Coraline [compact disc, unabridged] - Gaiman, Neil (Harper Children's Audio, 2002)
Looking for excitement, Coraline ventures through a mysterious door into a world that is similar, yet disturbingly different from her own, where she must challenge a gruesome entity in order to save herself, her parents, and the souls of three others.